Recombinant Influenza Vaccine and Influenza Outbreaks in US Nursing Homes: Results from a Pragmatic Cluster-Randomized Clinical Trial - Kevin W McConeghy; H Edward Davidson; Lisa Han; David H Canaday; Yasin Abul; Kaleen Hayes; Stefan Gravenstein (Open Forum Infectious Diseases, 2026)
Abstract Background Influenza outbreaks in U.S. nursing homes contribute substantially to morbidity, mortality, and operational strain. Recombinant influenza vaccine may reduce transmission in long-term care settings, but high-quality evidence to support this effect is limited. To compare the risk of influenza outbreaks (confirmed outbreak: 1+ laboratory-confirmed cases; suspected outbreak 2+ influenza-like illness cases) among nursing homes randomized to recombinant quadrivalent influenza vaccine (RIV4) versus standard-dose egg-based inactivated quadrivalent influenza vaccine (IIV4). Methods This study was a pragmatic, cluster-randomized clinical trial conducted across two influenza seasons (n=965 facilities 2019–2020 and n=1,023 in 2020–2021) in Medicare-certified U.S. nursing homes. Nursing homes with ≥50 long-stay residents and high proportions of adults aged ≥65 years were eligible and assigned to RIV4 or IIV4 for resident and staff vaccination. The outcome was facility-reported influenza outbreaks, assessed by monthly logs. Results During the 2019–2020 season, RIV4-assigned facilities experienced fewer suspected (148 [30.6%] vs 178 [37.0%]) and laboratory-confirmed (177 [36.6%] vs 214 [44.5%]) influenza outbreaks than IIV4 facilities. The adjusted relative risk (RR) for confirmed outbreaks was 0.82 (95% Confidence Interval, 0.71–0.96). In 2020–2021, confirmed outbreaks were rare (16 vs 15), and no significant differences were observed. COVID-19 outbreak risk did not differ between groups in either season. Conclusions RIV4 reduced influenza outbreak occurrence in U.S. nursing homes during a season with moderate influenza activity in older adults. No differences were observed during the low-circulation 2020–2021 season. These findings suggest that recombinant influenza vaccines may provide clinically meaningful facility-level benefits in long-term care settings during seasons with substantial influenza circulation.